The Colonial overlords : AD 1850-1900 - Time-Life Books (Amsterdam : Time-Life Books, 1990)
1. History of the world AD1850-1900
Includes Biblioraphy & Index
Bibliography: p. 170-171.
Basic Ed. Students
Keywords: History, Modern -- 19th century